Differences in the prices of residential premises on the primary and secondary real estate market in Wrocław between 2010 and 2017 - Zakrzewska-Półtorak, Alicja (Różnice w cenach lokali mieszkalnych na rynku pierwotnym i wtórnym we Wrocławiu w latach 2010-2017, 2019)
The purpose of the paper is to discuss the differences in the mean transaction price of 1 m2 of residential premises in selected territorial units of Wrocław (Poland) between 2010 and 2017, divided according to data from sales agreements on the primary and secondary market and depending on the usable area of the flat. The methods used in the paper include a descriptive method, simple statistical methods (e.g. coefficient of variation) and components of financial analysis. The data were taken from the AMRON Centre database and from Statistics Poland. In 2010-2017 the high demand for flats in Wrocław placed producers on a stronger position than buyers. Analysis revealed that the prices of bigger flats showed greater volatility over time than prices of smaller ones. Moreover growing differences in the average transaction price of 1 m2 of residential premises between flats constructed using new and old technology were observed, especially in the case of the larger ones
Biblioteka Regionalisty, 2019, Nr 19, s. 226-238
Keywords: Dolny Śląsk